Maqasid al-Shariah-Based Corporate Governance, Service Excellence, and Customer Satisfaction in Islamic Hospitality Sector - Titin Hardianti; Muslimin Kara; Nasrullah Bin Sapa; Jamaluddin Majid; Umar Sulaiman (Jurnal Ar-Ribh, 2026)
This study investigates the effect of Maqāṣid al-Sharīʿah–based Good Corporate Governance (GCG) on customer satisfaction, with service excellence as a mediating variable in the Islamic hospitality sector. The research adopts an explanatory quantitative design and is conducted at Sultan Alauddin Hotel & Convention Makassar. Data were collected from 212 customers using structured questionnaires and analyzed employing Partial Least Squares–Structural Equation Modeling (PLS-SEM). GCG is operationalized through three core dimensions: transparency, accountability, and responsibility, grounded in Maqāṣid al-Sharīʿah principles. The findings reveal that transparency does not have a significant direct effect on customer satisfaction but significantly influences it indirectly through service excellence. Accountability demonstrates a strong positive and significant effect on customer satisfaction, both directly and indirectly, indicating its dominant role in shaping customer perceptions. Conversely, responsibility does not significantly affect either service excellence or customer satisfaction. Furthermore, service excellence has a significant positive effect on customer satisfaction and serves as a crucial mediating variable linking governance practices to customer outcomes. These results suggest that the effectiveness of Maqāṣid al-Sharīʿah based governance depends on its practical implementation in service delivery. Integrating ethical governance with high-quality service enhances customer satisfaction and organizational sustainability. This study contributes to the literature by bridging Islamic governance principles with service management and provides practical insights for improving competitiveness in the Islamic hospitality industry.